War in Islamic Law: Muslim Jurists’ Theological Arguments for Its Obligation in Classical Literature - Wardani Wardani; Mujiburrahman Mujiburrahman; Muhammad Araby; Norhidayat Norhidayat (Universitas Islam Negeri Antasari Banjarmasin, 2025)
This article aims to analyze the Ḥanafīyah, Shāfiʿīyah, Mālikīyah, and Ḥanbalīyah jurists’ theological arguments supporting the obligation of jihād as a permanent war against non-Muslim communities from comparative, epistemological, and historical-context perspectives. The sources of this study are classical literature on Islamic law, analyzed through Karl Mannheim’s theory of the sociology of knowledge to identify the social contexts underlying the relationship between ideas and interests, ideas and social structures, as well as social location and historical experience. This article concludes that these theological arguments share similarities in their ultimate goal of establishing an ideal society capable of implementing Islamic law properly, as well as in their exclusive conceptions of disbelief (kufr) and polytheism (shirk). However, they differ regarding whether jihād constitutes a pillar of Islam and whether it may function as a means of seeking material gain. Epistemologically, these arguments are rooted in the Qur’an but were interpreted through an exclusive theological perspective aimed at constructing an ideal Muslim society, advancing the idea of Islamic universalism, and shaped by historical consciousness of the Prophet’s wars. This exclusive perspective within classical Islamic law on war should therefore be systematically reconstructed by removing its ideological and historical burdens and reinterpreting it in accordance with the spirit of humanity.